Quaternary ammonium salt intercalated bismuth sulfide microspheres for sodium-ion batteries and preparation method and application thereof

CN118084054BActive Publication Date: 2026-10-27ZHENGZHOU INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410228635.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-29
Publication Date
2026-10-27
Estimated Expiration
2044-02-29

AI Technical Summary

Technical Problem

专利CN116504966A公开了利用多层界面构筑优化硫化铋基锂电负极材料Bi2S3@C@X@PPy,金属X为Sn、Ni、Al、Sb、Ge、Mg或Zn,该合金材料一定程度上可以提升该材料储锂容量,但该方法所用原料多、制备工艺复杂,反复煅烧容易导致颗粒物在煅烧过程中团聚,从而影响合金材料在电池中的性能

Benefits of technology

1. 本发明中,以季铵盐作为插层剂插入层间调控硫化铋微球的晶面间距,而非简单复合反应生成物质提升性能。以插层的方式可确保材料性能优异的前提下,材料层间距得到扩大,硫化铋微球晶格(110)晶面层间距由初始的0.79 nm可扩大到1.3 nm;晶面层间距扩大的能够容纳更多的钠离子并且使钠离子更快的嵌入脱出,插层剂季铵盐已成功参与材料结构内部,且该插层剂在层间起到了支撑作用,缓解了材料的结构坍塌;本发明所制备的硫化铋微球粒径均一、成球性好、单分散性好、比表面积高,结构稳定性高;较高的比表面积和层间距提供了更多钠离子嵌入脱出的通道,从而具有更高的体积能量密度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118084054B_ABST
    Figure CN118084054B_ABST
Patent Text Reader

Abstract

The application provides a quaternary ammonium salt intercalation bismuth sulfide microsphere for sodium ion batteries and a preparation method and application thereof. The bismuth sulfide microsphere is prepared by using a bismuth source, a sulfur salt and a quaternary ammonium salt as raw materials, using a mixture of water and an organic solvent as a solvent, and reacting at 80-250 DEG C for 1-40 h to obtain a quaternary ammonium salt intercalation bismuth sulfide microsphere material for sodium ion batteries. The interlayer spacing of the crystal face layer of the obtained bismuth sulfide microsphere (110) can be expanded from the initial 0.79 nm to 1.3 nm. The bismuth sulfide microsphere with the expanded interlayer spacing has uniform particle size, good dispersity and large specific surface area. When the material is used as a negative electrode of a sodium ion battery, the discharge capacity of the battery under a current density of 0.1 A / g is 756.4 mAh / g, the initial discharge specific capacity under a current density of 10.0 A / g is 268.5 mAh / g, the capacity attenuation is 242 mAh / g after 200 cycles, the specific capacity retention rate is 90.13%, the obtained sodium ion battery has high specific capacity, good rate performance, high cycle stability and other excellent electrochemical performances. The synthesis process of the bismuth sulfide microsphere is simple and easy to operate, and has strong controllability, so the material is expected to be widely applied in the fields of lithium ion batteries, sodium ion batteries and other alkali metal ion batteries, thermoelectric materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of new energy sodium-ion electrode material technology, and relates to the preparation of sodium-ion battery anode materials, specifically to a quaternary ammonium salt intercalated bismuth sulfide microsphere for sodium-ion batteries, its preparation method and application. Background Technology

[0002] Lithium-ion batteries dominate the field of electrochemical energy storage. However, lithium-ion batteries are facing challenges such as scarce lithium resources and high prices. Therefore, it is of great significance to seek alternative batteries to lithium-ion batteries. Sodium-ion batteries are similar to lithium-ion batteries in terms of energy storage principle and are one of the important alternatives to sodium-ion batteries. Compared with lithium-ion batteries, sodium-ion batteries have the following advantages: (1) Sodium resources are abundant and inexpensive; (2) Sodium salt electrolytes have a conductivity that is about 20% higher than lithium salt electrolytes at the same concentration; (3) Sodium ions do not form an alloy layer with aluminum foil, and aluminum foil can be used as the current collector for the negative electrode, further reducing production costs; (4) The production process is similar, and lithium battery production equipment can be used, saving investment costs.

[0003] Electrode materials play a decisive role in the electrochemical performance of sodium-ion batteries. Among these, finding electrode materials with high specific capacity, high cycle stability, and good safety is of paramount importance. Currently, sodium-ion battery anode materials include carbon-based sodium storage anode materials, alloy-based sodium storage anode materials, and other sodium storage anode materials. For example, the hard carbon material reported by Komaba's research group (Adv. Funct. Mater, 2011, 21, 3859) exhibits a specific capacity of 240 mAh / g at a charge / discharge current density of 25 mA / g, and retains a capacity of 200 mAh / g after 100 cycles, demonstrating good cycle performance. Tin / carbon composite materials (J. Power Sources, 2013, 225, 316) show an initial capacity of 584 mAh / g when used as a sodium-ion battery anode. When amorphous TiO2 nanotubes (J. Phys. Chem. Lett., 2011, 2, 2560) are used as sodium-ion anode materials, the initial discharge capacity is 75 mAh / g, which increases to 150 mAh / g after 15 cycles, but the specific capacity is relatively low. A PBT / C composite material obtained by ball milling PBT with carbon (Electrochim. Acta., 2012, 78, 27) exhibits a charge / discharge specific capacity of 1187 / 690 mAh / g when applied to sodium-ion batteries, but the discharge capacity rapidly decays to 400 mAh / g after 40 cycles, indicating poor cycle stability.

[0004] Transition metal sulfides, such as bismuth sulfide (Bi₂S₃), possess high theoretical specific capacity for ion storage. However, these transition materials undergo structural volume expansion and pulverization during charge and discharge, resulting in less than ideal rate performance and cycle stability. In recent years, researchers have conducted modification work, including carbon and conductive polymer coating and heterostructure design. For example, patent CN115536063A discloses a method using the organic solvent N,N-dimethylformamide for solvothermal preparation and ultrasonic pulverization to obtain nanoflower-like bismuth sulfide nanocrystals. These nanocrystals exhibited high specific capacity when used in supercapacitors for energy storage, but did not demonstrate long-cycle charge-discharge stability. Patent CN116504966A discloses an optimized bismuth sulfide-based lithium-ion battery anode material Bi2S3@C@X@PPy constructed using a multilayer interface, where metal X is Sn, Ni, Al, Sb, Ge, Mg, or Zn. This alloy material can improve the lithium storage capacity of the material to some extent. However, this method uses many raw materials and has a complex preparation process. Repeated calcination can easily lead to the agglomeration of particulate matter during calcination, thus affecting the performance of the alloy material in the battery. Therefore, it is imperative to find other more feasible modification methods and expand the energy storage application of this material. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention proposes a method for preparing a negative electrode material for sodium-ion batteries with high specific capacity, high rate capability, and long cycle life. Specifically, it relates to a method for preparing quaternary ammonium salt intercalated bismuth sulfide microspheres for sodium-ion batteries. This morphology gives the electrode material good particle size uniformity and also solves the defects of material volume expansion and performance instability in existing technologies. To achieve the above objectives, the technical solution of this invention is implemented as follows: A method for preparing quaternary ammonium salt intercalated bismuth sulfide microspheres for sodium-ion batteries includes the following steps: (1) Add bismuth salt to the reaction solvent and stir until homogeneous to obtain the reaction solution; (2) Add the quaternary ammonium salt as an intercalating agent to the reaction solution of step (1) and mix evenly. After dissolving, add the sulfur salt and dissolve completely until the color turns into an orange-yellow mixed solution. (3) The mixed solution obtained in step (2) is loaded into a high-pressure reactor for reaction. After cooling, the mixture is separated, the precipitate is washed and dried to obtain sample powder.

[0006] Furthermore, the bismuth salt is bismuth carbonate, bismuth oxalate, or bismuth nitrate; the sulfur salt is sodium sulfide, sulfur, or thiourea; and the quaternary ammonium salt is any one of tetradecyltrimethylammonium bromide (TTAB), octadecyltrimethylammonium bromide (STAB), dodecyltrimethylammonium bromide (DTAB), decyltrimethylammonium bromide (DeTAB), n-octyltrimethylammonium bromide (CATAB), and tetramethylammonium bromide (TMAB).

[0007] By allowing different quaternary ammonium salt guest molecules to directly enter the interlayer, the interplanar spacing of the material is increased. The quaternary ammonium salt guest TTAB, which has the best performance, has the function of interlayer support and restricting the shuttle of polysulfides, which greatly improves the rate performance and cycle stability of the material. The intercalation of TTAB gives the material a larger interlayer structure, more sodium ion storage sites, delays the structural collapse of the material, and also inhibits the dissolution of polysulfides.

[0008] Furthermore, in step (1), the reaction solvent is a mixture of an organic solvent and deionized water, wherein the organic solvent is any one of methanol, ethylene glycol, ethanol, ethanolamine and polyethylene glycol-400, and the volume ratio of deionized water to organic solvent is (1-8): (1-8); the concentration of bismuth salt in the reaction solution is 0.1-0.4 mol / L.

[0009] Furthermore, the molar ratio of bismuth salt, sulfur salt and quaternary ammonium salt used in step (2) is (1-5): (1-10): (0.2-1).

[0010] Furthermore, in step (3), the reaction temperature in the high-pressure reactor is 80-250 ℃, the time is 1-40h, and the pressure is 2 MPa.

[0011] Furthermore, in step (3), the separation method is centrifugation or vacuum filtration; the washing method is washing three times each with deionized water and anhydrous ethanol; and the drying conditions are vacuum drying at 60 ℃ for 12 h.

[0012] Furthermore, sodium-ion battery quaternary ammonium salt intercalated bismuth sulfide microspheres prepared according to any of the above methods.

[0013] Furthermore, the bismuth sulfide microspheres have a particle size of 6-12 μm, and the microspheres are composed of nanospheres and nanorod clusters with certain gaps between the rods, which is beneficial for electrolyte wetting; the microspheres have a rich porosity structure and a large specific surface area.

[0014] Furthermore, due to the intercalation effect of different intercalating agents, the interlayer spacing variation calculated from XRD analysis shows that the interlayer spacing of the bismuth sulfide microspheres (110) is 1.3 nm.

[0015] Furthermore, the aforementioned sodium-ion battery quaternary ammonium salt intercalated bismuth sulfide microspheres are used in sodium / lithium-ion batteries, supercapacitors, or catalysis.

[0016] The present invention has the following beneficial effects: 1. In this invention, quaternary ammonium salts are used as intercalating agents to regulate the interlayer spacing of bismuth sulfide microspheres, rather than through simple composite reactions to generate substances that improve performance. Intercalation ensures excellent material performance while expanding the interlayer spacing; the interlayer spacing of the (110) bismuth sulfide microsphere lattice can be increased from the initial 0.79 nm to 1.3 nm. This increased interlayer spacing allows for the accommodation of more sodium ions and facilitates faster insertion and extraction. The quaternary ammonium salt intercalating agent has successfully participated in the material structure, and it provides support between layers, mitigating structural collapse. The bismuth sulfide microspheres prepared in this invention have uniform particle size, good sphericity, good monodispersity, high specific surface area, and high structural stability. The higher specific surface area and interlayer spacing provide more channels for sodium ion insertion and extraction, resulting in higher volumetric energy density.

[0017] 2. In a sodium-ion battery using the quaternary ammonium salt intercalated bismuth sulfide microsphere material of the present invention as the negative electrode, the large interlayer spacing formed by the intercalation expansion can provide a larger diffusion path, which is beneficial to Na + Ion insertion-extraction and electrolyte diffusion are employed to improve long-cycle performance at high current densities. The battery exhibits a discharge specific capacity of 756.4 mAh / g at a current density of 0.1 A / g; it maintains a discharge specific capacity of 208.4 mAh / g at a current density of 15 A / g; and at a current density of 10.0 A / g, the discharge specific capacity is 268.5 mAh / g, which decreases to 242 mAh / g after 200 charge-discharge cycles, with a specific capacity retention of 90.13%. The resulting sodium-ion battery demonstrates excellent electrochemical performance, including high specific capacity, good rate performance, and high cycle stability.

[0018] 3. The sodium-ion battery quaternary ammonium salt intercalated bismuth sulfide microsphere material of the present invention utilizes high-pressure mixed solvothermal processes. The interfacial reaction effect of the solvent within the reaction vessel restricts the nucleation, crystallization, and growth direction of the nanomaterials, thereby regulating the size and arrangement of the sheets. By using quaternary ammonium salts (chain-like and ionic) as intercalation units and adjusting the lattice spacing, the interlayer spacing is expanded. The operation method is simple, with high yield, low cost, no pollution, and strong structural controllability, making it suitable for large-scale coating production in factories.

[0019] 4. The quaternary ammonium salt intercalated bismuth sulfide microspheres with expanded interlayer spacing prepared in this invention are expected to have profound research significance and application prospects in fields such as supercapacitors, sodium / lithium-ion batteries, and catalysis. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0021] Figure 1 The images show the X-ray diffraction (XRD) patterns of bismuth sulfide of the present invention, where BS-TTAB is the XRD pattern of TTAB intercalated bismuth sulfide in Example 1; BS is the XRD pattern of ordinary bismuth sulfide material in Comparative Example 1, and the XRD pattern of Bi2S3 PDF#17-0320 standard card.

[0022] Figure 2 This is a scanning electron microscope (SEM) image of the quaternary ammonium salt intercalated bismuth sulfide microsphere material in Example 1 of the present invention.

[0023] Figure 3 The graph shows the specific surface area adsorption curves (BET) of bismuth sulfide materials, where a represents the single bismuth sulfide microsphere material of Comparative Example 1; and b represents the quaternary ammonium salt intercalated bismuth sulfide microsphere material of Example 1.

[0024] Figure 4 The constant current charge-discharge curves of a sodium-ion battery using bismuth sulfide microspheres as the negative electrode material at different current densities.

[0025] Figure 5 This is a rate performance curve of a sodium-ion battery using quaternary ammonium salt intercalated bismuth sulfide microspheres as the negative electrode material in Example 1 of the present invention; wherein curve BS-TTAB is the constant current charge-discharge curve of the sodium-ion battery using quaternary ammonium salt intercalated bismuth sulfide microspheres as the negative electrode material in Example 1 of the present invention, and BS is the constant current charge-discharge curve of the sodium-ion battery using bismuth sulfide as the negative electrode material in Comparative Example 1.

[0026] Figure 6 This is a cycle stability curve of a sodium-ion battery using quaternary ammonium salt intercalated bismuth sulfide microspheres as the negative electrode material in Example 1 of the present invention. Detailed Implementation

[0027] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0028] Example 1 The preparation method of quaternary ammonium salt intercalated bismuth sulfide microspheres for sodium-ion batteries in this embodiment is as follows: (1) Weigh out bismuth nitrate pentahydrate, add it to a mixed solution of deionized water and ethylene glycol (deionized water: ethylene glycol = 1: 1), add bismuth salt and stir for 30 min until the solid is completely dissolved. The concentration of the bismuth salt is 0.3 mol / L. (2) Weigh tetradecyltrimethylammonium bromide (TTAB) as an intercalating agent, add it to the solution in (1), and after dissolving, add thiourea. Dissolve completely until the color turns orange-yellow. The molar ratio of bismuth nitrate pentahydrate, thiourea and tetradecyltrimethylammonium bromide is 2.5: 8: 0.6. (3) The solution obtained in step (2) above was placed into a 100 mL autoclave with a polytetrafluoroethylene liner and sealed. It was kept at 100℃ for 12 hours and the pressure was 2 MPa. After the reaction was completed, the product was centrifuged. The centrifuged precipitate was washed three times each with deionized water and anhydrous ethanol and dried under vacuum at 60℃ for 12 h to obtain quaternary ammonium salt intercalated bismuth sulfide (BS-TTAB) microspheres.

[0029] The structure of the obtained quaternary ammonium salt intercalated bismuth sulfide (BS-TTAB) microsphere material is as follows: Figure 1 As shown, the XRD pattern of the quaternary ammonium salt intercalated bismuth sulfide microsphere material is consistent with PDF#17-0320 (bismuth sulfide PDF standard card). There are no other impurity peaks, and the peaks are sharp, indicating that the material has good crystallinity. Moreover, the (110) crystal plane shifts by 4.74° (from 11.44° to 6.7°) in the small angle direction, which is caused by the interlayer spacing expansion due to the intercalation of quaternary ammonium salt TTAB. At this time, the interlayer spacing increases from 0.79 nm in the standard state to 1.3 nm.

[0030] Figure 2 The image shows the SEM image of the intercalated bismuth sulfide microspheres prepared in this embodiment. It can be seen that the quaternary ammonium salt intercalated bismuth sulfide microspheres have a hierarchical structure and a uniform particle size distribution of 6~12 μm. The microspheres are composed of nanospheres and nanorod clusters, with certain gaps between the rods, which is beneficial for electrolyte wetting. Overall, they have a rich porosity structure and a large specific surface area.

[0031] Figure 3 This is a BET adsorption curve of the intercalated bismuth sulfide microspheres prepared in this embodiment and the comparative example. Figure 3 b represents the specific surface area of ​​the intercalated bismuth sulfide microspheres obtained in this embodiment, which is 15.5 m². 2 / g represents the specific surface area of ​​unmodified bismuth sulfide in Comparative Example 1 (2.31 m²). 2 More than 6 times that of (g).

[0032] A sodium-ion battery was assembled using the layered bismuth sulfide (BS-TTAB) microsphere material prepared in this embodiment as the negative electrode material. The half-cell preparation process was as follows: the self-made negative electrode sheet was composed of the negative electrode material prepared in this embodiment, conductive agent (acetylene black), and binder (polyvinylidene fluoride) in a ratio of 8:1:1; the sodium-ion battery was assembled in a sealed glove box filled with argon gas, and the water content and oxygen content were controlled below 0.1 ppm; after the half-cell was assembled conventionally with a self-made circular electrode with a diameter of 12 mm as the negative electrode, a Celgard 2400 with a diameter of 17 mm as the separator, and a pure sodium sheet as the counter electrode, electrochemical tests were performed.

[0033] The constant current charge-discharge curves of the prepared sodium-ion battery at different current densities are as follows: Figure 4 As shown; from right to left, the charge-discharge curves were measured at current densities of 0.1 A / g, 0.2 A / g, 0.4 A / g, 0.8 A / g, 1.0 A / g, 1.6 A / g, 2.0 A / g, 5.0 A / g, 10 A / g, and 15 A / g, where Voltage (V) is the voltage and Specific Capacity (mAh / g) is the specific capacity. According to Figure 4 The battery performance test results are shown in Table 1: Table 1:

[0034] During this process, the charge-discharge curves did not change significantly, indicating that the quaternary ammonium salt intercalated bismuth sulfide microsphere material exhibits excellent stability when used as a negative electrode material in sodium-ion batteries.

[0035] The rate performance curve of the sodium-ion battery obtained using the quaternary ammonium salt intercalated bismuth sulfide microsphere material of this embodiment as the negative electrode material is shown in the figure below. Figure 5 The BS-TTAB diagram shows the discharge specific capacity data measured at current densities of 0.1 A / g, 0.2 A / g, 0.4 A / g, 0.8 A / g, 1.0 A / g, 1.6 A / g, 2.0 A / g, 5.0 A / g, 10 A / g, and 15 A / g, from left to right. Cycle Numbers represent the charge-discharge cycle number, and Specific Capacity (mAh / g) represents the charge-discharge specific capacity. At a current density of 0.1 A / g, the specific capacity is 756.4 mAh / g. When the current density increases 150 times to 15 A / g, the specific capacity remains at 208.4 mAh / g. After five cycles at a current density of 15 A / g, when the current density is converted to 0.1 A / g, the specific capacity is approximately 600 mAh / g, which is 80% of the initial capacity, demonstrating good rate performance and cycle stability.

[0036] Figure 6 The charge-discharge data were obtained after 4910 charge-discharge cycles at a high current density of 10.0 A / g. Cycle Numbers represent the charge-discharge cycle number, and Specific Capacity (mAh / g) represents the discharge specific capacity. The initial discharge specific capacity was 268.5 mAh / g, which decreased to 242 mAh / g after 200 charge-discharge cycles, maintaining a specific capacity retention of 90.13%, demonstrating ultra-long cycle stability.

[0037] Example 2 The preparation method of the quaternary ammonium salt intercalated bismuth sulfide microsphere material for sodium-ion batteries in this embodiment is as follows: (1) Weigh out bismuth carbonate and add it to a mixed solution of deionized water and ethanol (deionized water: ethanol = 8: 1). Add bismuth salt and stir for 30 min until the solid is completely dissolved. The concentration of the bismuth salt is 0.1 mol / L.

[0038] (2) Weigh tetradecyltrimethylammonium bromide as an intercalating agent, add it to the solution in (1), and after dissolving, add sulfur. Dissolve completely until the color turns orange-yellow. The molar ratio of bismuth carbonate, sulfur and tetradecyltrimethylammonium bromide is 1:1:1. (3) The solution obtained in step (2) was placed in a 100 mL autoclave with a polytetrafluoroethylene liner and sealed. It was kept at 80 °C for 40 h under a pressure of 2 MPa. After the reaction, the product was washed three times each with deionized water and anhydrous ethanol and dried under vacuum at 60 °C for 12 h to obtain quaternary ammonium salt intercalated bismuth sulfide (BS-CTAB) microspheres. The (110) crystal plane shifted by 4.74° (from 11.44° to 6.7°) in the small angle direction. This was due to the interlayer spacing increase caused by the intercalation of quaternary ammonium salt CTAB. At this time, the interlayer spacing increased from 0.79 nm in the standard state to 1.3 nm.

[0039] The layered bismuth sulfide (BS-CTAB) microspheres prepared in this embodiment were used as the negative electrode material to assemble a sodium-ion half cell. The negative electrode sheet was composed of the negative electrode material, conductive agent and binder in a ratio of 8:1:1. The assembly process was the same as in Example 1.

[0040] In this example, the battery exhibits a discharge specific capacity of 730.87 mAh / g at a current density of 0.1 A / g, and still maintains a high discharge specific capacity of 302.48 mAh / g at a current density of 15 A / g. After 340 charge-discharge cycles at a current density of 5.0 A / g, the specific capacity retention rate is 89.26%.

[0041] Example 3 The preparation method of the quaternary ammonium salt intercalated bismuth sulfide microsphere material for sodium-ion batteries in this embodiment is as follows: (1) Weigh out bismuth oxalate heptahydrate, add it to a mixed solution of deionized water and methanol (deionized water:methanol=1:4), add bismuth salt and stir for 30 min until the solid is completely dissolved. The concentration of the bismuth salt is 0.2 mol / L. (2) Weigh decyltrimethylammonium bromide (DeTAB) as an intercalating agent, add it to the solution in (1), dissolve it, then add sodium sulfide, and dissolve it completely until the color turns orange-yellow. The molar ratio of bismuth oxalate, sodium sulfide and decyltrimethylammonium bromide is 1:1:0.2. (3) The solution obtained in step (2) was placed in a 100 mL autoclave with a polytetrafluoroethylene liner and sealed. It was kept at 250 °C for 1 h. The product was washed three times each with deionized water and anhydrous ethanol and then vacuum dried at 60 °C for 12 h to obtain quaternary ammonium salt intercalated bismuth sulfide (BS-DeTAB) microspheres with adjustable interlayer spacing. The (110) crystal plane shifted by 4.74° (from 11.44° to 6.7°) in the small angle direction, which was caused by the interlayer spacing expansion due to the intercalation of quaternary ammonium salt DeTAB. At this time, the interlayer spacing increased from 0.79 nm in the standard state to 1.3 nm.

[0042] The layered bismuth sulfide (BS-DeTAB) microspheres prepared in this embodiment were used as the negative electrode material to assemble a sodium-ion half cell. The negative electrode sheet was composed of the negative electrode material, conductive agent and binder in a ratio of 8:1:1. The assembly process was the same as in Example 1.

[0043] In this example, the battery exhibits a discharge specific capacity of 700.48 mAh / g at a current density of 0.1 A / g, and still maintains a high discharge specific capacity of 200.97 mAh / g at a current density of 15 A / g. After 340 charge-discharge cycles at a current density of 5.0 A / g, the specific capacity retention rate is 85.27%.

[0044] Example 4 The preparation method of the quaternary ammonium salt intercalated bismuth sulfide microsphere material for sodium-ion batteries in this embodiment is as follows: (1) Weigh out bismuth nitrate pentahydrate and add it to a mixed solution of deionized water and ethanolamine (deionized water: ethanolamine = 2: 1). Add bismuth salt and stir for 30 min until the solid is completely dissolved. The concentration of the bismuth salt is 0.3 mol / L.

[0045] (2) Weigh out n-octyltrimethylammonium bromide (CATAB) as an intercalating agent, add it to the solution in (1), and after dissolving, add thiourea. Dissolve completely until the color turns orange-yellow. The molar ratio of bismuth nitrate, thiourea and n-octyltrimethylammonium bromide is 1:10:1. (3) The solution obtained in step (2) was placed in a 100 mL autoclave with a polytetrafluoroethylene liner and sealed. The autoclave was kept at 150 °C for 12 h. The product was washed three times each with deionized water and anhydrous ethanol and then vacuum dried at 60 °C for 12 h to obtain quaternary ammonium salt intercalated bismuth sulfide (BS-CATAB) microspheres. The (110) crystal plane shifted by 4.74° (from 11.44° to 6.7°) in the small angle direction, which was caused by the interlayer spacing expansion due to the intercalation of quaternary ammonium salt CATAB. At this time, the interlayer spacing increased from 0.79 nm in the standard state to 1.3 nm.

[0046] The layered bismuth sulfide (BS-CATAB) microspheres prepared in this embodiment were used as the negative electrode material to assemble a sodium-ion half cell. The negative electrode sheet was composed of the negative electrode material, conductive agent and binder in a ratio of 8:1:1. The assembly process was the same as in Example 1.

[0047] In this example, the battery exhibits a discharge specific capacity of 707.21 mAh / g at a current density of 0.1 A / g, and still maintains a high discharge specific capacity of 202.17 mAh / g at a current density of 15 A / g. After 340 charge-discharge cycles at a current density of 5.0 A / g, the specific capacity retention rate is 86.59%.

[0048] Example 5 This embodiment provides a method for preparing quaternary ammonium salt intercalated bismuth sulfide microspheres for sodium-ion batteries, as follows: (1) Weigh out bismuth oxalate heptahydrate and add it to a mixed solution of deionized water and polyethylene glycol-400 (deionized water: polyethylene glycol-400 = 1: 8). Add bismuth salt and stir for 30 min until the solid is completely dissolved. The concentration of the bismuth salt is 0.4 mol / L.

[0049] (2) Weigh out octadecyltrimethylammonium bromide (STAB) as an intercalating agent, add it to the solution in (1), and after dissolving, add sulfur. Dissolve completely until the color turns orange-yellow. The molar ratio of bismuth oxalate heptahydrate, sulfur and octadecyltrimethylammonium bromide is 5:10:1. (3) The solution obtained in step (2) was placed in a 100 mL autoclave with a polytetrafluoroethylene liner and sealed. The autoclave was kept at 200 °C for 30 h. The product was washed three times each with deionized water and anhydrous ethanol and then vacuum dried at 60 °C for 12 h to obtain quaternary ammonium salt intercalated bismuth sulfide (BS-STAB) microspheres. The (110) crystal plane shifted by 4.74° (from 11.44° to 6.7°) in the small angle direction, which was caused by the interlayer spacing expansion due to the intercalation of quaternary ammonium salt STAB. At this time, the interlayer spacing increased from 0.79 nm in the standard state to 1.3 nm.

[0050] The layered bismuth sulfide (BS-STAB) microspheres prepared in this embodiment were used as the negative electrode material to assemble a sodium-ion half cell. The negative electrode sheet was composed of the negative electrode material, conductive agent and binder in a ratio of 8:1:1. The assembly process was the same as in Example 1.

[0051] In this example, the battery exhibits a discharge specific capacity of 691.47 mAh / g at a current density of 0.1 A / g, and still maintains a high discharge specific capacity of 198.99 mAh / g at a current density of 15 A / g. After 340 charge-discharge cycles at a current density of 5.0 A / g, the specific capacity retention rate is 89.47%.

[0052] Example 6 This embodiment provides a method for preparing quaternary ammonium salt intercalated bismuth sulfide microspheres for sodium-ion batteries, as follows: (1) Weigh out bismuth nitrate pentahydrate, add it to a mixed solution of deionized water and ethylene glycol (deionized water: ethylene glycol = 8: 1), stir for 30 min until the solid is completely dissolved, and the concentration of the bismuth salt is 0.3 mol / L; (2) Weigh out tetramethylammonium bromide (TMAB) as an intercalating agent, add it to the solution in (1), and after dissolving, add thiourea. Dissolve completely until the color turns orange-yellow. The molar ratio of bismuth nitrate, thiourea and tetramethylammonium bromide is 5:10:0.2. (3) The solution obtained in step (2) was placed in a 100 mL autoclave with a polytetrafluoroethylene liner and sealed. It was kept at 80 °C for 40 h. The product was washed three times each with deionized water and anhydrous ethanol and then vacuum dried at 60 °C for 12 h to obtain quaternary ammonium salt intercalated bismuth sulfide (BS-TMAB) microspheres. The (110) crystal plane shifted by 4.74° (from 11.44° to 6.7°) in the small angle direction, which was caused by the interlayer spacing expansion due to the intercalation of quaternary ammonium salt TMAB. At this time, the interlayer spacing increased from 0.79 nm in the standard state to 1.3 nm.

[0053] The layered bismuth sulfide (BS-TMAB) microspheres prepared in this embodiment were used as the negative electrode material to assemble a sodium-ion half cell. The negative electrode sheet was composed of the negative electrode material, conductive agent and binder in a ratio of 8:1:1. The assembly process was the same as in Example 1.

[0054] In this example, the assembled battery exhibited a discharge specific capacity of 702.66 mAh / g at a current density of 0.1 A / g, and a discharge specific capacity of 201.49 mAh / g at a current density of 15 A / g. After 340 charge-discharge cycles at a current density of 5.0 A / g, the specific capacity retention was 90.43%.

[0055] Comparative Example 1 The difference between this comparative example and Example 1 is that no intercalating agent was added. The preparation method of bismuth sulfide microspheres is as follows: (1) Weigh out bismuth nitrate pentahydrate, add it to a mixed solution of deionized water and ethylene glycol (deionized water: ethylene glycol = 1: 1), add bismuth salt and stir for 30 min until the solid is completely dissolved. The concentration of the bismuth salt is 0.3 mol / L. (2) Add thiourea to the solution in (1) and dissolve it completely until the color turns orange-yellow. The molar ratio of bismuth nitrate pentahydrate to thiourea is 2.5:8. (3) The solution obtained in step (2) above was placed into a 100 mL autoclave with a polytetrafluoroethylene liner and sealed. It was kept at 100 °C for 12 h and the pressure was 2 MPa. After the reaction was completed, the product was centrifuged. The centrifuged precipitate was washed three times each with deionized water and anhydrous ethanol and dried under vacuum at 60 °C for 12 h to obtain a single bismuth sulfide microsphere material.

[0056] The XRD pattern of the unmodified bismuth sulfide monosulfide in this comparative example is shown below. Figure 1 As shown in the figure, the XRD pattern of the obtained bismuth sulfide material is consistent with PDF#17-0320 (bismuth sulfide PDF standard card). Apart from this, there are no other impurity peaks, and the peaks are sharp, indicating that the material has good crystallinity and that there is no shift in the various crystal planes, indicating that the interlayer spacing is unchanged.

[0057] The specific surface area of ​​the unmodified bismuth sulfide in this comparative example, as shown in Figure 3a, is 2.31 m². 2 / g, approximately 1 / 6 of the specific surface area of ​​the bismuth sulfide microspheres obtained in Example 1.

[0058] The bismuth sulfide microspheres prepared in this comparative example were used as the negative electrode material to assemble a sodium-ion half-cell. The negative electrode sheet was composed of the negative electrode material of this comparative example, conductive agent, and binder in a ratio of 8:1:1. The assembly process was the same as in Example 1.

[0059] In this comparative example, the discharge capacity of the assembled battery is as follows: Figure 5As shown in the BS, at a current density of 0.1 A / g, the initial discharge specific capacity is 730 mAh / g. After 5 cycles, the current densities are switched sequentially to 0.2 A / g, 0.4 A / g, 0.8 A / g, 1.0 A / g, 1.6 A / g, 2.0 A / g, 5.0 A / g, 10 A / g, and 15 A / g. The discharge specific capacity at a current density of 5 A / g is close to 0. After 5 cycles at a current density of 15 A / g, switching to a current density of 0.1 A / g, the discharge specific capacity recovers to about 350 mAh / g, which is about 50% lower than the initial discharge capacity. The cycle performance is poor and the capacity retention is low.

[0060] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the scope of the conventions and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing quaternary ammonium salt intercalated bismuth sulfide microspheres for sodium-ion batteries, characterized in that, Includes the following steps: (1) Add bismuth salt to the reaction solvent and stir until homogeneous to obtain the reaction solution; (2) Add the quaternary ammonium salt as an intercalating agent to the reaction solution of step (1) and mix evenly. After dissolving, add thiourea and dissolve completely until the color turns into an orange-yellow mixed solution. (3) The mixed solution obtained in step (2) is loaded into a high-pressure reactor for reaction. After cooling, the mixture is separated, the precipitate is washed and dried to obtain sample powder. The bismuth salt is bismuth nitrate; the quaternary ammonium salt is any one of tetradecyltrimethylammonium bromide, octadecyltrimethylammonium bromide, dodecyltrimethylammonium bromide, decyltrimethylammonium bromide, and n-octyltrimethylammonium bromide. In step (1), the reaction solvent is a mixture of ethylene glycol and deionized water, and the volume ratio of deionized water to organic solvent is 1:

1. In step (3), the reaction temperature in the high-pressure reactor is 100 ℃, the time is 12 h, and the pressure is 2 MPa.

2. The method for preparing quaternary ammonium salt intercalated bismuth sulfide microspheres for sodium-ion batteries according to claim 1, characterized in that: The concentration of the bismuth salt in the reaction solution is 0.1-0.4 mol / L.

3. The method for preparing quaternary ammonium salt intercalated bismuth sulfide microspheres for sodium-ion batteries according to claim 1, characterized in that: The molar ratio of bismuth salt, thiourea and quaternary ammonium salt used in step (2) is (1-5):(1-10):(0.2-1).

4. The method for preparing quaternary ammonium salt intercalated bismuth sulfide microspheres for sodium-ion batteries according to claim 1, characterized in that: In step (3), the separation method is centrifugation or vacuum filtration; the washing method is washing three times each with deionized water and anhydrous ethanol; the drying conditions are vacuum drying at 60 ℃ for 12 h.

5. Quaternary ammonium salt intercalated bismuth sulfide microspheres for sodium-ion batteries prepared by the method according to any one of claims 1-4.

6. The quaternary ammonium salt intercalated bismuth sulfide microspheres for sodium-ion batteries according to claim 5, characterized in that: The bismuth sulfide microspheres have a particle size of 6-12 μm.

7. The quaternary ammonium salt intercalated bismuth sulfide microspheres for sodium-ion batteries according to claim 5, characterized in that: The interlayer spacing of the (110) crystal planes of bismuth sulfide microspheres is 1.3 nm.

8. The application of the quaternary ammonium salt intercalated bismuth sulfide microspheres for sodium-ion batteries according to claim 5 in sodium-ion batteries.

Citation Information

Patent Citations

  • Nanometer flower-shaped bismuth sulfide, preparation method and application

    CN115536063A

  • Method for constructing and optimizing bismuth sulfide-based lithium battery negative electrode material by utilizing multi-layer interface

    CN116504966A